2011 Aerospace Conference 2011
DOI: 10.1109/aero.2011.5747561
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Remaining Useful Life by using Wavelet Packet Decomposition and HMMs

Abstract: This paper deals with an estimation of the Remaining Useful Life of bearings based on the utilization of the Wavelet Packet Decomposition (WPD) and the Mixture of Gaussians Hidden Markov Models (MoG-HMM). The raw data provided by the sensors are first processed to extract features by using the wavelet packet decomposition. This latter provides a more flexible way of time-frequency representation and filtering of a signal, by allowing the use of variable sized windows and different detail levels. The extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…where the quantity ( ), which takes into account the duration dependent forward variable ( ), is calculated through (17). The reader is referred to Rabiner's work [13] for the interpretation on the observation parameters reestimation formulas.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…where the quantity ( ), which takes into account the duration dependent forward variable ( ), is calculated through (17). The reader is referred to Rabiner's work [13] for the interpretation on the observation parameters reestimation formulas.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…To overcome this drawback, a modified version of HMM, which takes into account an estimate of the duration in each state, has been proposed in the works of Tobon-Mejia et al [16][17][18][19]. Thanks to the explicit state sojourn time modeling, it has been shown that it is possible to effectively estimate the RUL for industrial equipment.…”
Section: Introductionmentioning
confidence: 99%
“…4-(a). Note that this classification is not totally binary as it may exist prognostic methods based on the fusion of more than one approach [19], see the In model-based prognostic, the physical component or system and its degradation phenomenon are represented by a set of mathematical laws. The obtained behavioral model is then used to predict the future evolution of the degradation [20,21].…”
Section: Prognostic Approachesmentioning
confidence: 99%
“…With the aim of investigating the case in which a failure condition is unknown during the training phase, we consider bearing monitoring data taken from the NASA benchmark repository [42], which have been used in several other works [37,[43][44][45]. As the available data set does not contain any explicit information about the bearing conditions, we use the detection time of the failure state as a measure of model performance.…”
Section: Real Datamentioning
confidence: 99%
“…It has to be noted that frequency [35] (i.e., Fourier transform) or time-frequency [36,37] (i.e., wavelet transform) domain features could be used as well.…”
Section: Feature Extraction and Dimensionality Reductionmentioning
confidence: 99%